2016
DOI: 10.3991/ijet.v11i03.5370
|View full text |Cite
|
Sign up to set email alerts
|

"Once upon a Time there was..." A Digital World for Junior High School Learners

Abstract: Abstract-This paper looks into what Junior HighSchool learners think of the Web 2.0 tool "Storyboard" for digital story telling purposes and investigates the extent to which it can enhance their receptive and productive skills of reading and writing in the English language. Fifty one randomly selected students, who created a digital story based on a relevant instructive scenario, and their teachers took part in the research. The quantitatively analyzed teachers' and students' interviews results and learners' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Digital story telling allows the user/author to practice critical thinking in selecting the story topic, elaborating ideas in text, image and sound and consolidate new knowledge, which can boost students' motivation and engagement. Batsila and Tsihouridis (2016), for instance, found that using a social media tool for digital storytelling in an English class helped students enhance their reading and writing skills, their interest in writing and struggling students' self-confidence. Similarly, Vazquez-Cano (2012) explored how middle school students' use of Twitter in Spanish language, social sciences and natural sciences classes sparked their creativity and self-directed learning.…”
Section: Social Media For Active Learningmentioning
confidence: 99%
“…Digital story telling allows the user/author to practice critical thinking in selecting the story topic, elaborating ideas in text, image and sound and consolidate new knowledge, which can boost students' motivation and engagement. Batsila and Tsihouridis (2016), for instance, found that using a social media tool for digital storytelling in an English class helped students enhance their reading and writing skills, their interest in writing and struggling students' self-confidence. Similarly, Vazquez-Cano (2012) explored how middle school students' use of Twitter in Spanish language, social sciences and natural sciences classes sparked their creativity and self-directed learning.…”
Section: Social Media For Active Learningmentioning
confidence: 99%
“…Actively participating on social media can increase students’ motivation and engagement in various content areas (Schwarz & Caduri, 2016). Using social media for digital storytelling in an English class helped students embrace their creativity (Batsila & Tsihouridis, 2016). Teachers noted an increase in the adolescent students’ interest in writing, even recognizing an improvement in struggling students’ self-confidence.…”
Section: Opportunities For Student Learning With Social Mediamentioning
confidence: 99%
“…In a study examining the effectiveness of using technology for digital storytelling in improving third graders' writing skills, Yamaç and Ulusoy (2017) found stories written in collaboration with others were stronger in quality than those written individually. Similarly, other studies have found students benefit from peer collaboration (Batsila and Tsihouridis, 2016;Beam and Williams, 2015;Hitchcock et al, 2016;Howell et al, 2017;Kervin and Mantei, 2016;Sessions et al, 2016). Teachers have access to data that inform them about their students' writing progress.…”
Section: Online Writing Applicationsmentioning
confidence: 69%